High Order Cesarean Section: Is It Associated With More Operative Complications Then Lower Order Cesarean Section - Akram, Umbreen; Khan, Sumaira; Khalil, Adiba Akhtar; Siraj, Asifa; Khan, Samina Rehan; Yaqub, Umairah (Pakistan Armed Forces Medical Journal, 2023)
Objective: To detect complications associated with higher order versus lower order cesarean section.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital, Mardan Pakistan, from Mar to Aug 2021.Methodology: The study was conducted on 210 women, the participants were categorised into two Groups: Group-I (Higherorder), who had undergone fourth and fifth cesarean sections, and Group-II (Lower order), who had undergone second and third Cesarean Sections. The presence of complications were noted in both the Groups.Results: The frequency of higher and lower-order Cesarean Sections was 75(35.7%) and 135(64.3%), respectively. Mean gestational age and parity were 38.96±0.69 weeks and 3.49±2.12, respectively. Dense omental adhesion was a significantly common complication in both Groups. Scar dehiscence was 35(25.9%) among Group-II. There was no significant association between the high-order cesarean section and its complications.Conclusion: The higher-order repeat cesarean section was not associated with more intraoperative complications when compared with lower-order cesarean section in our study. Certain factors like maternal age, parity and gestational age affect the intraoperative complications of the cesarean section.